Comparative analysis of the behavior of drop panel-slab system and beam-slab system using spectrum response method - Satria Dayvano Mangelep; Sudarno P Tampubolon; Setyadi (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2026)
The height of a building is influenced by the needs of the room. The height of a building can be reduced by planning the structural system to be used. The use of a structural system in a building will affect the behavior of the structure when given an earthquake load. The drop-panel slab is a structural system where the slab is directly connected to the column without resting on the beam. In this system, the load received by the floor slab is directly distributed to the column. The advantage of the drop-panel slab system is easier installation of formwork and reinforcement. In addition, the drop-panel slab system will reduce the clear height of the room because there are no beams protruding under the slab. However, the drop-panel slab system has disadvantages such as limited slab span and weak in resisting shear forces. While the slab-beam system is a structural system where the slab will rest on the beam to distribute the load. The slab-beam system has advantages such as a longer span and better strength to withstand shear because there are beams as components that resist shear forces. A comparison of the behavior of the beam-slab and drop panel -slab system will be analyzed using the spectrum response method ETABS V.22 software to determine the value of the structure vibration period, base shear, the story drift, and the deflection value that occurs on the floor slab. The slab-beam structural system demonstrates a higher fundamental period in the x-direction and a lower period in the y-direction when compared with the slab-drop panel system. The value of the base shear force on the beams is also smaller than in the panel drop-drop system due to the smaller effective weight of the building as well. Likewise, the story drift that occurred in the smaller slab-beam system was 17,39% in the x-direction and 20,50% in the y-direction compared to the slab-drop panel system. This shows that the slab-beam system can be more reliable in reducing the story drift value due to earthquake loads. The value of the deflection of the floor slab calculated on the floor that experienced the greatest moment showed that the system of slabs experienced an instantaneous deflection of 10.58 mm, 26.84% bigger than the drop panel-slab system that experienced an instantaneous deflection of 7,74 mm. So that the service ability of the slab-drop panel system is better than the slab-beam system.